Dual-chamber leadless pacing: Atrioventricular synchrony in preclinical models of normal or blocked atrioventricular conduction - Reddy, Vivek Y.; Neuzil, Petr; Booth, Daniel F.; Knops, Reinoud E.; Doshi, Rahul N.; Rashtian, Mayer; Exner, Derek V.; Banker, Rajesh S.; Nair, Devi; Hadadi, Cyrus A.; Badie, Nima; Yang, Weiqun; et al. (Heart rhythm, 2023)
Dual-chamber leadless pacemakers (LPs) require robust communication between distinct right atrial (RA) and right ventricular (RV) LPs to achieve atrioventricular (AV) synchrony. The purpose of this preclinical study was to evaluate a novel, continuous implant-to-implant (i2i™) communication methodology for maintaining AV-synchronous, dual-chamber DDD(R) pacing by the 2 LPs. RA and RV LPs were implanted and paired in 7 ovine subjects (4 with induced complete heart block). AV synchrony (% AV intervals <300 ms) and i2i communication success (% successful i2i transmissions between LPs) were evaluated acutely and chronically. During acute testing, 12-lead electrocardiographic and LP diagnostic data were collected from 5-minute recordings, in 4 postures and 2 rhythms (AP-VP and AS-VP, or AP-VS and AS-VS) per subject. Chronic i2i performance was evaluated through 23 weeks postimplant (final i2i evaluation period: week 16–23). Acute AV synchrony and i2i communication success across multiple postures and rhythms were median [interquartile range] 100.0% [100.0%–100.0%] and 99.9% [99.9%–99.9%], respectively. AV synchrony and i2i success rates did not differ across postures (P = .59, P = .11) or rhythms (P = 1, P = .82). During the final i2i evaluation period, the overall i2i success was 98.9% [98.1%–99.0%]. Successful AV-synchronous, dual-chamber DDD(R) leadless pacing using a novel, continuous, wireless communication modality was demonstrated across variations in posture and rhythm in a preclinical model.